2009
DOI: 10.1038/ki.2009.157
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor Nrf2 is protective during ischemic and nephrotoxic acute kidney injury in mice

Abstract: Oxidative stress is involved in acute kidney injury due to ischemia-reperfusion and chemotherapy-induced nephrotoxicity. To investigate their basic mechanisms we studied the role of nuclear factor-erythroid 2-p45-related factor 2 (Nrf2), a redox-sensitive transcription factor that regulates expression of several antioxidant and cytoprotective genes. We compared the responses of Nrf2-knockout mice and their wild-type littermates in established mouse models of ischemia-reperfusion injury and cisplatin-induced ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
184
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(199 citation statements)
references
References 41 publications
(43 reference statements)
6
184
0
2
Order By: Relevance
“…In addition to promoting oxidative stress, impaired Nrf2 function contributes to intra-renal inflammation and progression of kidney disease. In fact ablation of Nrf2 gene results in intensification of oxidative stress, inflammation, and renal injury in diabetic animals [17] and heightens the severity of ischemic and nephrotoxic acute kidney injury [18].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to promoting oxidative stress, impaired Nrf2 function contributes to intra-renal inflammation and progression of kidney disease. In fact ablation of Nrf2 gene results in intensification of oxidative stress, inflammation, and renal injury in diabetic animals [17] and heightens the severity of ischemic and nephrotoxic acute kidney injury [18].…”
Section: Introductionmentioning
confidence: 99%
“…The renal protective effect of Nrf2 is supported by the fact that Nrf2 knockout mice develop lupus-like autoimmune nephritis [33] and show intensified oxidative stress with accelerated renal injury when subjected to experimental diabetes mellitus [34]. Further, Nrf2-deficient mice subjected to ischemic and nephrotoxic insults show impaired upregulation of antioxidant pathways, with more severe acute kidney injury and higher mortality, compared to wild-type controls [35]. Finally, recent studies have demonstrated the salutary effects of a low dose of Nrf2 inducer dh404 on oxidative stress, kidney fibrosis, endothelial dysfunction, and vascular abnormalities in CKD animals [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…Nrf2 deiciency is associated with an increased mortality accompanied by augmented kidney dysfunction and vascular permeability. Liu et al [13] demonstrated that Nrf2 deiciency enhances susceptibility to both ischemic and nephrotoxic acute kidney injury and identiies this transcription factor as a potential therapeutic target in these injuries.…”
Section: Implications Of Nrf2 Transcription Factor In Diabetic Complimentioning
confidence: 99%
“…On the other hand, Nrf2 plays a protective role in experimental acute kidney injury, and this protection is mediated, in part, through an endogenous antioxidant pathway [2,13].…”
Section: Implications Of Nrf2 Transcription Factor In Diabetic Complimentioning
confidence: 99%
See 1 more Smart Citation